Investigation of the Mechanical Properties of AISI 316 Austenitic Stainless Steel and St 37 Low Carbon Steel Dissimilar Joint by Friction Stir Welding - A.H. Khosrovaninezhad; M. Shamanian; A. Rezaeian; M. Atapour (Journal of Advanced Materials in Engineering, 2015)
This paper reports on the mechanical properties of the dissimilar joints between AISI 316 austenitic stainless steel and St 37 low carbon steel achieved using friction stir welding technique. The welding was carried out by means of rotational speed of 800 rpm and linear speeds of 50,100,150 mm/min. EDS and XRD techniques were employed in order to determine possible phase transformations. Tensile test, shear punch test and microhardness measurements were conducted to evaluate the mechanical properties of the joints. The results of phase investigations showed that no carbide and brittle phase were detected at the joint boundary. Also, tensile test results demonstrated that failure occurred in the St 37 base metal. According to the shear punch test, the highest ultimate shear strength and yield shear strength was achieved for the sample welded at rotational speed of 800 rpm and linear speed of 150 mm/min, while this sample showed the least elongation. In addition, the highest microhardness was measured in the stir zone of austenitic stainless steel sample welded in the above mentioned welding condition, which can be attributed to the decrease in grain size caused by recrystallization process.